The safety and efficacy of prolonged use of one-way speaking valves. Issue 4 (July 2021) - O'Connor, Lauren Rachel; Morris, Norman; Paratz, Jennifer
Abstracts: Background: One-way speaking valves were first engineered to improve communication in patients with tracheostomies. More recently, additional indications for one-way speaking valves have been explored, including improving ventilation, weaning, and reducing aspiration; however, safety and adverse events have not been well defined. Objectives: The aim of this study was to examine the cardiorespiratory changes that occur with prolonged use of a one-way speaking valve in relation to safety and efficacy. Methods: A prospective observational study of adult patients (n = 20) was carried out in a tertiary level intensive care unit. Continuous monitoring of cardiorespiratory parameters, including heart rate (beats per minutes), respiratory rate (breaths per minute), systolic, diastolic, and mean arterial pressure (mmHg), and oxygen saturations (%), was conducted for 2 h whilst participants used a one-way speaking valve. The participants then continued to use the one-way speaking valve as long as tolerated. Data are reported as median and range (non-normative data) or as mean ± standard deviation (normative data). Results: The time to tracheostomy was 17.5 (range = 7–54) days after the initiation of mechanical ventilation, and the time to first use of the one-way speaking valve was 11.4 days (standard deviation = 5.46) after tracheostomy. The participants tolerated using a one-way speaking valve (for more than 2 h) after a median of 2 (range = 1–8) days from first use. There were no significant changes to any cardiorespiratory parameters over the 2-h period and also no adverse events in this study whilst participants used one-way speaking valves for up to 17 (range = 5.5–17) hours. Conclusions: The prolonged use of a one-way speaking valve is safe for patients who reached a threshold of 2 h.